Benedetta [videorecording (DVD)] - Verhoeven, Paul, 1938-; Birke, David; Dudley, Anne, 1956-; Efira, Virginie, 1977-; Rampling, Charlotte, 1946-; Patakia, Daphné; Wilson, Lambert; Rabourdin, Olivier, 1959-; Chevillotte, Louise; Pierre, Hervé, 1955-; Courau, Clotilde; Brown, Judith C. (IFC Films, 2022)
Based on a true story, a 17th-century nun becomes entangled in a forbidden lesbian affair with a novice. But it is Benedetta's shocking religious visions that threaten to shake the Church to its core.